Education in the post-pandemic of covid 19: a hybrid practice? An experience report from the state education system of bahia - Jesus dos Santos, Juvenicio; do Espírito Santo, Eniel (Seven Editora, 2023)
This work reflects a critical reflective look at the pedagogical coordination of public basic education in the context of the pandemic and post-pandemic and aims to understand the limits and possibilities for hybrid teaching practices in basic education in the post-pandemic of covid 19, to know these possibilities that emerged within the school in the post-pandemic context and promote scientific and technological education mediated by TDIC. It is configured as an experience report from the performance of the pedagogical coordination in 01 (one) public school, in the interior of Bahia, which takes reference to the period between 2020 and 2022. It presupposes that, in the post-pandemic period, hybrid teaching practices can emerge within the school, considering that the teacher has accessed other possibilities to manage student learning, has known numerous digital interfaces, that is, has reference to digital interfaces that he did not previously have, and that you can add them to your pedagogical practice and promote hybrid teaching practices within the classroom. DOI: https://doi.org/10.56238/alookdevelopv1-005